Entre o verdadeiro histórico e a imaginação criadora: ilustrações sobre história e cultura dos povos indígenas em livros didáticos de História - Leonardo Machado Palhares (2012)
This research analyzes images (illustrations) about history and culture of indigenous people in history textbooks. Two textbook collections destined to the first years of elementary school in Brazil (from second to fifth grade) have been selected to this analysis: História, Imagem &Texto [History, Image & Text] and História no Dia-a-Dia [History in Daily Life]. Both collections appear in the Guia do Plano Nacional do Livro Didático [Guide of National Textbook Plan] of 2004 and 2010. The analysis considers the probable impacts of the law 11.645/08 on the approaches of indigenous peoples history and culture. In the research there are reflections on textbook considering the studies of Fonseca (1993), Bittencourt (1993 e 2008), Munakata (1997), Chartier (1990 e 1999), Fonseca (2001), Siman (2001), Choppin (2004), Miranda e Luca (2004), Bezerra e Luca (2007), Cassiano (2007), Darnton (2008), Luca (2009), Mattos (2009), Batista e Galvão (2009), Filho (2009), which are fundamental to the understanding of researches about book, especially about Brazilian textbooks and its material constitution, as well as the actors involved in their production and the relations betweenpublishing houses, authors, readers, and the state. Concerning the indigenous topic in history textbooks, were considered important the studies developed by Almeida (2010), Bergamaschi (2011), Freire (2009), Bittencourt (2001; 2011), Carneiro da Cunha (1992), Cruz (2009),Gobbi (2007), Gonçalves (2005), Grupioni (2004), Melo (2008) e Summer (2004). Regarding the research on historical illustrations, we have considered fundamental the studies about visualities and visual culture founded in Arbach (2007), Boitello Júnior (2000), Burke (2004), Bohnsack (2010), Joly (2008), Knauss (2005; 2008), Meneses (2003; 2012), Panofsky (2001) e Rodrigues (2011). Trough the analysis of illustrations on indigenous peoples history and culture we discuss the representations of indigenous, their history in the context of the studyof history in Brazil, and the diversity of their cultures. This research considers illustrations as vestiges of their time and as documents/ sources in the studies of History and History Teaching illustrations produced to be used in a media context of the history textbook, in which the historical source is regarded in the dimensions of truth and imagination.